A multi agent recommender system that utilises consumer reviews in its recommendations. (21st February 2008) - Zhang, Debbie; Simoff, Simeon; Aciar, Silvana; Debenham, John
Consumer reviews, opinions and shared experiences in the use of a product form a powerful source of information about consumer preferences that can be used for making recommendations. A novel approach, which utilises this valuable information sources first time to create recommendations in recommender agents was recently developed by Aciar et al. (2007). This paper presents a general framework of this approach. The proposed approach is demonstrated using digital camera reviews as an example.